2019
DOI: 10.1111/1748-5967.12343
|View full text |Cite
|
Sign up to set email alerts
|

The bimodal adult activity of Monochamus alternatus (Coleoptera: Cerambycidae) caught in pheromone traps in Jeju can be explained by the competitive attractiveness of dying pine trees

Abstract: The Japanese pine sawyer, Monochamus alternatus Hope (Coleoptera: Cerambycidae), is known to be the primary vector of pinewood nematode Bursaphelenchus xylophilus (Steiner & Buhrer) Nickle that causes pine wilt disease. Adult activity of M. alternatus caught in a pheromone trap on Jeju Island of Korea showed a bimodal form with the first peak in mid to late June and the second peak in mid to late September. The two peaks were separated between mid and late August, showing a valley. Accumulated degree‐days pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…It might be somewhat overestimated since he showed that the HCW at 6 d after hatching ranged from 1.1 to 2.8 mm in the same rearing study. In other words, if the first instars were in the just hatched state, they would be difficult to develop into the range discussed earlier for 6 d because the development time for the first instar is longer than 6 d at below 26°C (Kwon 2017). The range was overlapped largely with the HCW range of second and third instars (1.5–1.9 and 2.1–2.9 mm, respectively, based on his study).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It might be somewhat overestimated since he showed that the HCW at 6 d after hatching ranged from 1.1 to 2.8 mm in the same rearing study. In other words, if the first instars were in the just hatched state, they would be difficult to develop into the range discussed earlier for 6 d because the development time for the first instar is longer than 6 d at below 26°C (Kwon 2017). The range was overlapped largely with the HCW range of second and third instars (1.5–1.9 and 2.1–2.9 mm, respectively, based on his study).…”
Section: Discussionmentioning
confidence: 99%
“…They covered them with steel mesh in the site and collected the first sample at 10 d after field treatment, taking maximum 20 d in total. Because the development time of M. alternatus eggs and the first instar at 26°C are 6.7 and 7.1 d, respectively, according to Kwon (2017), the first sample of Liu et al (2008) might have included lots of the second instars. Consequently, the second HCW presented by Liu et al (2008) would be actually the third HCW, which well corresponded with the third HCW of Kojima and Katagiri (1964) and the present study.…”
Section: Discussionmentioning
confidence: 99%
“…trapping or spraying) are likely to target both species simultaneously. However, continued warming may impact voltinism or increase duration of flight periods by reducing flight synchrony (Azrag et al., 2020; Dell & Davis, 2019), which could have negative consequences for host trees with high late season evapotranspirative demands (Kwon et al., 2019). Differences between timing of flight periods observed in Colorado and those in areas where mortality due to pine wilt disease is more frequent warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, two native species, that have never had a relationship with PWN, have come to transmit PWN in the country since the invasion: M. saltuarius Gebler as the vector of PWN in the central region and M. alternatus Hope in the southern region of the country [16]. The Forests 2022, 13, 955 2 of 17 pinewood nematode, transmitted by M. alternatus, has been causing immense damage to coniferous forests in Jeju Island since 2013 [17]. PWD causes a higher mortality rate than the pine caterpillar (Dendrolimus spectabilis Butler) or pine needle gall midge (Thecodiplosis japonensis Uchida & Inouye), causing great economic damage to the Korean forestry industry.…”
Section: Introductionmentioning
confidence: 99%